2007
DOI: 10.1177/0734016807311905
|View full text |Cite
|
Sign up to set email alerts
|

Misbehavior at School and Delinquency Elsewhere

Abstract: This article addresses the relationship between problem behaviors inside school (misbehavior) and outside school (delinquency). Self-report data about 12 types of misbehavior and 9 types of delinquency were collected among 1,978 secondary school students in The Netherlands of which 1,385 were followed up one year later. The relationship between misbehavior and delinquency was not studied before in such detail. The findings show that there is a general relationship between misbehavior inside school and delinque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 19 publications
2
23
0
3
Order By: Relevance
“…For instance, O’Donnell, Hawkins, and Abbott (1995) found that low levels of school bonding and academic achievement at ages 12 to 13 predicted serious delinquency and drug use one year later. Using a sample of students from the Netherlands, Weerman, Harland, and van der Laan (2007) found that school misbehavior in seventh and ninth grade predicted serious delinquency outside of school one year later. Borowsky, Ireland, and Resnick (2002) found that grade retention, school problems, GPA, school connectedness, and skipping school predicted violence one year later, net of baseline measures of violence perpetration.…”
Section: School Disengagement As a Predictor Of Dropout Delinquencymentioning
confidence: 99%
“…For instance, O’Donnell, Hawkins, and Abbott (1995) found that low levels of school bonding and academic achievement at ages 12 to 13 predicted serious delinquency and drug use one year later. Using a sample of students from the Netherlands, Weerman, Harland, and van der Laan (2007) found that school misbehavior in seventh and ninth grade predicted serious delinquency outside of school one year later. Borowsky, Ireland, and Resnick (2002) found that grade retention, school problems, GPA, school connectedness, and skipping school predicted violence one year later, net of baseline measures of violence perpetration.…”
Section: School Disengagement As a Predictor Of Dropout Delinquencymentioning
confidence: 99%
“…For example, in a recent Dutch study, students who misbehaved in the classroom were more likely to engage in antisocial behaviour outside the classroom as well (Weerman, Harland, & van der Laan, 2007). Misbehaviour in the classroom, poor school performance, and antisocial behaviour have each been linked to poor self-control or the inability to regulate behaviour (Felson & Staff, 2006).…”
Section: Special Education Needsmentioning
confidence: 99%
“…For instance, some adolescents who withdraw from stress and distress addict to substance and internet use (2,3) , whereas some act out in the form of misbehavior and delinquency (4) . In particular, research fi ndings have shown that there are gender differences: boys tend to employ externalizing and risk-taking behavior as ventilation, while girls tend to internalize stress and become depressed (5,6) .…”
mentioning
confidence: 99%